THE CULTURAL ADAPTATION, VALIDATION, AND RELIABILITY OF THE TURKISH VERSION OF THE LIFE SPACE ASSESSMENT - Bilek, Furkan; Cetisli-Korkmaz, Nilufer; Senol, Hande; Soylemez, Betul (Turkey Assoc Physiotherapists, 2022)
Purpose: The aim of this study was to determine the reliability and validity of the Turkish version of the Life Space Assessment (LSA) in older adults. Methods: A hundred fifty-two elderly people with a mean age was 72.81 +/- 7.63 years recruited to the study. Following the forward-backward translation procedure, the LSA scores were compared with a number of mobility and general health related variables, including the Physical Activity Scale for the Elderly (PASE) and the 36-Item Short Form Health Survey (SF-36) to test the concurrent validity. Results: None of the items in the LSA were changed. Cronbach's a coefficient was 0.714 for the initial evaluation. The intraclass correlation coefficient for the test-retest reliability was 0.991 with a 95% confidence interval of 0.986-0.994. It found that the highest consistence was obtained in the equipment scores. All the subscores of LSA found to have a significant relationship with PASE scores and SF-36 subscores. A very strong positive correlation found between the total score of LSA and PASE (r = 0.896). Similarly, a very strong correlation observed between SF-36's subscore physical function, and LSA composite score (r = 0.841). Conclusion: The results of the study showed that the Turkish version of LSA has strong measurement features and that the LSA is a sensitive tool for assessing the life domains of elderly individuals related to their general health and physical activity level. Therefore, the Turkish version of the LSA could be used as a reliable and valid scale in research and practice areas related to elderly people.
YAŞAM ALANI DEĞERLENDIRME ÖLÇEĞİ’NİN TÜRKÇE VERSİYONUNUN GEÇERLİK VE GÜVENİRLİK ÇALIŞMASI
Keywords: Activities of Daily Living; Aged; Health; Life Space Assessment